Estradiol and zinc-doped nano hydroxyapatite as therapeutic agents in the prevention of osteoporosis; oxidative stress status, inflammation, bone turnover, bone mineral density, and histological alterations in ovariectomized rats - Elghareeb, Mona M.; Elshopakey, Gehad E.; Elkhooly, Tarek A.; Salama, Basma; Samy, Alaa; Bazer, Fuller W; Elmetwally, Mohammed A; Almutairi, Mikhlid H.; Aleya, Lotfi; Abdel-Daim, Mohamed M.; Rezk, Shaymaa (Frontiers in Physiology, 2022)
Osteoporosis (OP) is a severe health problem and the most popular therapeutic strategy for OP is hormone replacement (Estrogen), however, its risk of increasing reproductive cancers. Hydroxyapatite (HA) nanoparticles have a similar chemical structure to the bone mineral component and can be used as a new remedy for OP. This study investigated the osteoporosis-protective potential of nano zinc hydroxyapatite (ZnHA) and/or estradiol (E2) replacement therapy. Thirty-five adult female rats were assigned into 5 groups (n=7): 1) control group; 2) ovariectomized group (OVX); 3) OVX received oral estradiol replacement therapy (OVX/E2); 4) OVX received ZnHA replacement therapy (OVX/ZnHA) and 5) OVX received both estradiol and ZnHA replacement therapy (OVX/E2+ZnHA). After three months of treatment, serum bone markers and estrogen levels, as well as oxidative/antioxidant, and inflammatory cytokines were determined. Additionally, femoral expression of estrogen receptors alpha and beta (ESR1; ESR2), receptor activator of nuclear factor-kappa B (RANKL) ligand, and osteoprotegerin (OPG), bone mineral density (BMD), histological alterations, and immunohistochemical expression of vascular endothelial growth factor (VEGF) and proliferating cell nuclear antigen (PCNA) were assessed. ALP, PINP, Ca, and Ph concentrations improved significantly (P<0.05) in all treatment groups, especially in the OVX/E+ZnHA group. MDA and NO were higher in OVX rats, while SOD activity and GSH were lower (P<0.05). E2 alone or with znHA-NPS ZnHA restored the estimated antioxidant molecules and cytokines toward normal levels in OVX rats (P<0.05). On the other hand, E2 and ZnHA increased OPG and OC expression in femurs, while decreasing ESR1, ESR2, and NF-kB expression (p< 0.05). The combination treatment was superior in the restoration of normal femoral histoarchitecture and both cortical and trabecular BMD (P< 0.05). Overall, the combined therapy of OVX/E2+ZnHA was more effective than the individual treatments in attenuating excessive bone turnover and preventing osteoporosis.